Simultaneous Laparoscopic Cholecystectomy and Endovascular Infrarenal Aortic Aneurysm Repair - Illuminati, Giulio; Calio', Francesco G.; Pasqua, Rocco; Nardi, Priscilla; Fratini, Chiara; Urciuoli, Paolo (Frontiers in Surgery, 2021)
Background/Aim: With the increasing use of endovascular aneurysm repair (EVAR) and the availability of laparoscopic cholecystectomy (LC) for treating abdominal aortic aneurysms (AAA) and cholelithiasis, respectively, the association between these elective treatments is not yet well-defined. Thus, this study aimed to evaluate the results of elective and simultaneous EVAR and LC. Methods: Thirteen patients (mean age, 72 years) with concomitant large and asymptomatic AAA and asymptomatic cholelithiasis underwent simultaneous EVAR and LC. Results: Post-operative mortality was absent, and the morbidity rate was 7%. The mean total duration of the procedure was 142 min. The mean duration of fluoroscopy was 19 min, and the mean radiation dose was 65 mGy. The mean amount of iodinated contrast injected was 49 mL. The timing of oral fluid intake was 28 h (range, 24–48 h) and that of the oral low-fat diet was 53 h (range, 48–72 h). No patient presented with an aortic graft infection during the entire follow-up period (mean duration, 41 months). The mean length of post-operative hospital stay was 6 days (range, 5–8 days). Late survival was 85%, and the exclusion of AAA was 100%. Conclusion: Simultaneous EVAR and LC can be performed safely, allowing effective and durable treatment under both AAA and cholelithiasis conditions.